Increase the Vocabulary of Elementary School Students - Ismoilova, Surmakhon; Khuzhamova, Gulsevar (European Journal of Life Safety and Stability (2660-9630), 2021)
In our article, we try to correct the shortcomings of students’ speech, increase the vocabulary of students, teach them the correct use of words and phrases, and at the same time make the use of dictionaries a vital necessity, develop skills and abilities to use them, and thus enrich their vocabulary.